A novel PCR-RFLP assay for the detection of the single nucleotide polymorphism at position+1440 in the human CXCR2 gene - Viana, Aline C.; Kim, Yeon J.; Cirelli, Joni A.; Orrico, Silvana R. P.; Curtis, Karen C.; Cano, Veridiana S. P.; Valentini, Sandro Roberto [UNESP]; Scarel-Caminaga, Raquel Mantuaneli (Springer, 2007)
We designed a novel PCR-RFLP assay to genotype for the CXCR2 +1440 (G/A) single nucleotide polymorphism, which provides a simple, low-cost, practical, and reproducible method. Allele frequencies in healthy Brazilian individuals were found to be 0.65% for allele A and 0.35% for allele G.
Keywords: PCR-RFLP; polymorphism; CXCR2; human